The Implementation of Wordwall Media in Learning Morphology (Ilmu Sharaf): A Qualitative Study on PBA Students: Implementation of Wordwall Media in Learning Morphology (Ilmu Sharaf): A Qualitative Study on PBA Students (Al-IRTIQA: Journal of Arabic Education and Linguistics, 2026)
This study aims to examine the implementation of Wordwall as a digital learning media in teaching Ilmu Sharaf to students of Arabic Language Education (PBA). The study is grounded in the increasing demand for innovative instructional media that can facilitate the comprehension of sharaf concepts, which are inherently abstract and linguistically complex. This research adopts a qualitative method with a library research approach, focusing on the systematic review and critical analysis of relevant scholarly sources, including peer-reviewed journal articles, academic books, and prior empirical studies. The findings reveal that Wordwall serves as an effective instructional tool in enhancing students’ learning motivation, active participation, and conceptual understanding through its interactive features, such as gamified quizzes and digital exercises. Moreover, its integration supports the implementation of student-centered learning and promotes flexible learning environments. Nevertheless, its effectiveness is contingent upon educators’ pedagogical competence in designing appropriate learning content and the availability of adequate technological infrastructure. In conclusion, Wordwall represents a viable and effective alternative for technology-enhanced learning in Ilmu Sharaf instruction.